Analisis Moral Kerja Pada Dosen - Fatwa Tentama; Subardjo Subardjo (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
This study aims to describe the work morale of the lecturer at the "X" University, to examine the construct validity and construct reliability of the work moral scale, to know the contribution of work morale aspects and indicators in reflecting the work morale of the lecturer, and to test the work moral measurement model. Methods of data collection using the moral work scale. Data analysis was done by using Structural Equation Modeling (SEM) with second order confirmatory factor analysis (2nd Order CFA). The results show that lecturers at university "X" have morale in high category. The dominant aspect that reflects work morale is the aspect of responsibility with the indicator is the ability to finish the job and the job is done as well as possible. The lowest aspect that reflects work morale is morale with an indicator of willpower in work and pleasure in work.